Hypereosinophilia in Solid Tumors—Case Report and Clinical Review - Zalewska, Ewa; Obołończyk, Łukasz; Sworczak, Krzysztof (Frontiers in Oncology, 2021)
Background: Renal cell cancer may cause various paraneoplastic syndromes; however, paraneoplastic hypereosinophilia occurs exceedingly rare. Thus far, only two cases of clear cell renal cell carcinoma (CCRCC) associated with hypereosinophilia have been reported. In this paper, we present a case of paraneoplastic hypereosinophilia associated with renal cell carcinoma and a review of the reported cases of hypereosinophilia in solid tumors. Methods: The review is based on an electronic literature search performed in the PubMed database in September 2020 with the following key terms: eosinophilia & neoplasm; eosinophilia & cancer; eosinophilia & paraneoplastic syndrome. Papers were included based on screening the titles and/or abstracts. We also included the case of our patient in the analysis. Case presentation: A 68-year-old Caucasian female patient with recurrent CCRCC was admitted to our Clinic for exacerbating dyspnea and chest and right upper abdominal pain, accompanied by confusion. Preliminary blood tests showed an increased white blood cell count of 40,770/μl, and an increased eosinophil count of 6,530/μl indicating eosinophilia. Several tests were carried out to rule out the noncancer causes of hypereosinophilia. The temporal appearance of eosinophilia and the recurrence of CCRCC without any other apparent potential causes led to the diagnosis of paraneoplastic hypereosinophilia. Despite treating with high doses of corticosteroids, only a transient decrement in eosinophil count was observed along with further deterioration of the patient’s condition. The patient succumbed to the disease 6 months following the tumor surgery and 2 months after the diagnosis of hypereosinophilia and tumor recurrence. Conclusion: Our observations are in agreement with the majority of reports showing that the occurrence of eosinophilia following tumor resection may indicate a poor prognosis, tumor recurrence, and rapid disease progression.